2014
DOI: 10.1093/pan/mpu003
|View full text |Cite
|
Sign up to set email alerts
|

Relating Latent Class Assignments to External Variables: Standard Errors for Correct Inference

Abstract: Latent class analysis is used in the political science literature in both substantive applications and as a tool to estimate measurement error. Many studies in the social and political sciences relate estimated class assignments from a latent class model to external variables. Although common, such a “three-step” procedure effectively ignores classification error in the class assignments; Vermunt (2010, “Latent class modeling with covariates: Two improved three-step approaches,” Political Analysis 18:450–69) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 64 publications
4
99
0
2
Order By: Relevance
“…Through the simulation study, we evaluate the relative performance of the two methods when the within-class distribution of a continuous Z exhibits skewness, excess kurtosis, and bimodality, respectively. The results for bimodality are given in the supplementary material as they are similar to results for the single latent variable case (Bakk et al, 2014; but with slightly lower coverage in situations with poor class separation. We also conduct simulations using the modified BCH approach (detailed results in the supplementary material) as previous research confirmed its robustness to violations of distributional assumptions (Asparouhov & Muthén, 2014b;.…”
Section: Study 2: Violation Of the Normality Assumption About Zsupporting
confidence: 58%
See 4 more Smart Citations
“…Through the simulation study, we evaluate the relative performance of the two methods when the within-class distribution of a continuous Z exhibits skewness, excess kurtosis, and bimodality, respectively. The results for bimodality are given in the supplementary material as they are similar to results for the single latent variable case (Bakk et al, 2014; but with slightly lower coverage in situations with poor class separation. We also conduct simulations using the modified BCH approach (detailed results in the supplementary material) as previous research confirmed its robustness to violations of distributional assumptions (Asparouhov & Muthén, 2014b;.…”
Section: Study 2: Violation Of the Normality Assumption About Zsupporting
confidence: 58%
“…One possible explanation is that at low entropy levels, the differences between classes are over-stated, which leads to an underestimation of the classification error (Bakk et al, 2014;Vermunt, 2010). Standard errors are severely underestimated using the modified BCH approach, although using a sandwich variance estimator provides a slight correction.…”
Section: Comparison Of Methods: Evidence From Simulation Studiesmentioning
confidence: 99%
See 3 more Smart Citations